Menakar Partisipasi Politik Masyarakat Kota Medan Terhadap Pemilihan Walikota Medan Tahun 2020 - Nasution, Faiz Albar; Thamrin, Muhammad Husni; Ritonga, Alwi Dahlan (Talenta Publisher, 2020)
This study examines the political participation of the Medan City community to the Medan mayor elections. One indicator of the success of the elections, can be seen from the community participation in the exercise of the right of choice. However, voters ' participation in Medan city elections since reform to date, tends to have a low level of participation. The phenomenon, quite indicating that the community of the city of Medan has no orientation in using the right to select the regional head election. Therefore, the estimative participation of voters in the city elections in Medan year 2020 interesting to learn, to be a reference and reflection material in the press of the number of abstainers in Medan. This research is done by a qualitative method of descriptive. Data collection techniques using secondary data in the form of journals, documents, newspapers and primary data through in-depth interviews to the informant that originated from the agency of elections, political and social organisations. Data analysis using the Miles and Huberman techniques are: data reduction, data display and draw conclusions. The results of the study showed the community participation in Medan is dominated by participation in voting and total apathy. In addition, the factors that determine the level of participation in the upcoming elections 2020 are; Government, the party's role in political recruitment and the update of voters data.